Al-Qur’an dan Kaum Difabel (Tunanetra) - Muhammad Haris Fauzi (Prodi Ilmu al-Qur'an dan Tafsir, 2020)
Blind people have always been considered as a person who is not useful to those around them. Psychologically, the negative view of society causes blind people to be insecure and have negative behavior as well. Of course as a result, their relationship with Allah. as well as with fellow humans to be less good. As for the blind people themselves, they feel rejected because their conditions are different from others. Furthermore, they usually become more sensitive to external evaluations. They feel dissatisfied with the situation. However, the Koran is here to emphasize the position of blind people who have the same position, obligations and rights as other creatures. Although in some cases, blind people also get rukhsah not to carry out orders like other Muslims do, for example when fighting, they are allowed not to follow them.